2012
DOI: 10.1128/iai.00581-12
|View full text |Cite
|
Sign up to set email alerts
|

Subtilase Cytotoxin Enhances Escherichia coli Survival in Macrophages by Suppression of Nitric Oxide Production through the Inhibition of NF-κB Activation

Abstract: e Subtilase cytotoxin (SubAB), which is produced by certain strains of Shiga-toxigenic Escherichia coli (STEC), cleaves an endoplasmic reticulum (ER) chaperone, BiP/Grp78, leading to induction of ER stress and caspase-dependent apoptosis. SubAB alters the innate immune response. SubAB pretreatment of macrophages inhibited lipopolysaccharide (LPS)-induced production of both monocyte chemoattractant protein 1 (MCP-1) and tumor necrosis factor ␣ (TNF-␣). We investigated here the mechanism by which SubAB inhibits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 64 publications
1
27
0
Order By: Relevance
“…MyD88-deficient mice are highly susceptible to infection with a broad range of pathogenic microorganisms (von Bernuth et al, 2008). In addition, NO contributes to protection against infection with bacteria including Mycobacterium tuberculosis, L. monocytogenes and certain strains of Shiga toxigenic E. coli (Boockvar et al, 1994;El Kasmi et al, 2008;Tsutsuki et al, 2012) and macrophage cells in response to LPS produce the mediator, which stimulates MyD88-dependent pathway via TLR4 (Jacobs and Ignarro, 2001;Akira et al, 2006). Taken together, in this report the results of MyD88 downregulation suggest that the trichothecene DON, which is frequently detected in cereals (Yazar and Omurtag, 2008), is able to trigger dysregulation of innate immune response mediated through the TLR-MyD88 signaling pathway, leading to impairment of the host systems responsible for protection against infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MyD88-deficient mice are highly susceptible to infection with a broad range of pathogenic microorganisms (von Bernuth et al, 2008). In addition, NO contributes to protection against infection with bacteria including Mycobacterium tuberculosis, L. monocytogenes and certain strains of Shiga toxigenic E. coli (Boockvar et al, 1994;El Kasmi et al, 2008;Tsutsuki et al, 2012) and macrophage cells in response to LPS produce the mediator, which stimulates MyD88-dependent pathway via TLR4 (Jacobs and Ignarro, 2001;Akira et al, 2006). Taken together, in this report the results of MyD88 downregulation suggest that the trichothecene DON, which is frequently detected in cereals (Yazar and Omurtag, 2008), is able to trigger dysregulation of innate immune response mediated through the TLR-MyD88 signaling pathway, leading to impairment of the host systems responsible for protection against infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide (NO) produced by cells of the innate immunity system plays a role in protection against various pathogens (Boockvar et al, 1994;El Kasmi et al, 2008;Tsutsuki et al, 2012). Our previous study demonstrated that DON inhibited LPS-induced NO production by mouse macrophage cells and also reduced the LPSinduced reporter gene activity of interferon-β (IFN-β) which is essential for LPS-induced expression of inducible NO synthase (iNOS) gene (Sugiyama et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The catalytic A subunit is a serine protease that cleaves BiP/GRP78, a regulator of the stress response in the ER, and ultimately leads to cell death. SubAB may also be involved in altering host immune responses, as it was shown to prevent antibody secretion from B cells (350) and to suppress NO in macrophages, leading to the hypothesis that it may promote the survival of STEC in macrophages (351).…”
Section: Pathogenesismentioning
confidence: 99%
“…SubAB-dependent BiP cleavage is inhibited by brefeldin A (BFA), a Golgi complex-disrupting agent (15,16). SubAB-induced ER stress due to BiP cleavage causes activation of stress sensor proteins, followed by the induction of various cellular events leading to cell damage, e.g., transient inhibition of protein synthesis (17), G 0 /G 1 cell cycle arrest (15,17), caspase-dependent apoptosis via mitochondrial membrane damage (18), activation of Akt-NF-B signaling (19), downregulation of gap junction expression (20), activation of RNA-dependent protein kinase (PKR)-like ER kinase (PERK) followed by caspase-dependent apoptosis (12), and inhibition of lipopolysaccharide (LPS)-stimulated NO production through inhibition of NF-B nuclear translocation and inducible nitric oxide synthase (iNOS) expression (21).…”
mentioning
confidence: 99%